2003
DOI: 10.1002/app.12107
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymerization of methyl methacrylate onto rubber‐wood fiber using H2O2 and Fe2+ as an initiator system

Abstract: Methyl methacrylate (MMA) was successfully grafted onto rubber-wood fiber in a free-radical solution polymerization initiated by ferrous ion and hydrogen peroxide. The effects of the reaction parameters (reaction temperature, reaction period, influence of hydrogen peroxide, ferrous ammonium sulfate, and monomer concentrations) were investigated. The grafting percentage showed dependency on H 2 O 2 , Fe 2ϩ , and monomer concentrations, as well as reaction temperature and reaction period. The optimum reaction te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Cellulose, which is a naturally occurring complex polysaccharide, is biodegradable and the most abundant renewable organic raw material at low costs in the world. Modification of cellulose by graft copolymerization and direct chemical modification techniques allows one to chemically change the cellulose chain by introducing functional groups, which leads to new cellulose products with new properties [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose, which is a naturally occurring complex polysaccharide, is biodegradable and the most abundant renewable organic raw material at low costs in the world. Modification of cellulose by graft copolymerization and direct chemical modification techniques allows one to chemically change the cellulose chain by introducing functional groups, which leads to new cellulose products with new properties [15].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature survey has revealed that considerable efforts, such as alkylation reactions, bamboo's use with coupling agents, and graft copolymerizations, have been made in this area . Among them, the graft copolymerization technique dominates because it reduces the surface energy of cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the graft copolymerization technique dominates because it reduces the surface energy of cellulose. It also improves the compatibility of the composite materials of bamboo and plastic . With an initiator system, Abu‐Ilaiwi et al used H 2 O 2 and Fe 2+ to graft‐copolymerize methyl methacrylate onto wood fiber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl methacrylate, as an important vinyl monomer, has been successfully grafted onto holo cellulose by a ceric ion initiator system reported recently 19. Abu‐Illai20 has recently reported on grafting of methyl methacrylate onto rubberwood fiber using H 2 O 2 and Fe 2+ as the initiator system. Polymethyl methacrylate (PMMA) is very useful in biomedical applications such as dental fillings, contact lenses, eye lens replacement, and other dental and optical applications.…”
Section: Introductionmentioning
confidence: 99%